2013
DOI: 10.1002/masy.201200017
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Quenching Methods Toward exo‐Olefin‐Terminated Polyisobutylene

Abstract: Abstractexo‐Olefin‐terminated polyisobutylene was obtained directly from living isobutylene polymerizations by addition of a quenching compound to the living chain ends. Three broad classes of compounds were evaluated including hindered bases such as hindered pyridines and piperidines, N‐hydro‐2,5‐disubstitutedpyrroles, and sulfides, ethers, and silylethers. The proposed mechanism of quenching unique to each class was discussed, with supporting kinetic, spectroscopic, and structure‐based evidence presented. Hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 24 publications
1
16
0
Order By: Relevance
“…1) on the formation of exo-olen end group through the end-quenching of TiCl 4 -co-initiated living cationic polymerization of IB. [33][34][35] Among these bases, the highest efficiency showed PMP and TMP which yielded PIB with 100% of exo-olen end groups and can be used at relatively concentrated conditions ([IB] # 1.5 M). 34,35 The low efficiency of DTBP is consistent with its steric hindrance that prevents the efficient b-H abstraction, on the one hand.…”
Section: Polyisobutylenementioning
confidence: 99%
“…1) on the formation of exo-olen end group through the end-quenching of TiCl 4 -co-initiated living cationic polymerization of IB. [33][34][35] Among these bases, the highest efficiency showed PMP and TMP which yielded PIB with 100% of exo-olen end groups and can be used at relatively concentrated conditions ([IB] # 1.5 M). 34,35 The low efficiency of DTBP is consistent with its steric hindrance that prevents the efficient b-H abstraction, on the one hand.…”
Section: Polyisobutylenementioning
confidence: 99%
“…The exo‐olefin terminated PIB is also referred to as “highly reactive” PIB (HR PIB), since it readily reacts with maleic anhydride in a thermal “ene” reaction to produce PIB succinic anhydride that can be converted to polyisobutenylsuccinimide, used as ashless dispersants. In the recent years, several research groups have reported on new catalyst systems for the synthesis of HR PIB . Some major drawbacks for the new HR PIB process systems include low process temperatures and/or use of polar chlorinated solvents that present serious limitations for industrial application .…”
Section: Introductionmentioning
confidence: 99%
“…In the recent years, several research groups have reported on new catalyst systems for the synthesis of HR PIB. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] Some major drawbacks for the new HR PIB process systems include low process temperatures and/or use of polar chlorinated solvents that present serious limitations for industrial application. [26][27][28] Recently, we reported an ethylaluminum dichloride (EADC)Ábis(2-chloroethyl) ether (CEE) complex as a fully hydrocarbon soluble catalyst that in conjunction with tert-butyl chloride (t-BuCl) initiator in hexanes at 0-20 8C gave HR PIB with quantitative yields and up to 92% exo-olefin end-functionality.…”
mentioning
confidence: 99%
“…HRPIBs synthesis by process (B) could also be conducted via specific termination reaction after completion of living cationic polymerization coinitiated with TiCl 4 by addition of allyltrimethylsilane, strong hindered bases, such as 2,5-disubstituted pyrroles, hindered aliphatic tertiary amines, partially hindered pyridines or sulfides, or modification from tert-chloro-terminated functional PIB chains reaction. [63][64][65][66][67][68][69][70][71][72][73][74][75] The TMPCl/FeCl 3 /iPrOH initiating system has been recently developed in our research group to achieve living cationic polymerization of IB in CH 2 Cl 2 /hexane mixture at 280 C. 19 Very interestingly, the chain-transfer-dominated cationic polymerization of IB with H 2 O/FeCl 3 /iPrOH initiating system in nonpolar hydrocarbons at 240 to 20 C has also been achieved in our research group, leading to direct synthesis of HRPIBs with more than 90 mol % of exo-olefin. 62 It indicates that living cationic polymerization of IB co-initiated by FeCl 3 could be transformed to chain-transfer-dominated process by changing reaction conditions.…”
Section: Introductionmentioning
confidence: 99%
“…HRPIBs synthesis by process (B) could also be conducted via specific termination reaction after completion of living cationic polymerization coinitiated with TiCl 4 by addition of allyltrimethylsilane, strong hindered bases, such as 2,5‐disubstituted pyrroles, hindered aliphatic tertiary amines, partially hindered pyridines or sulfides, or modification from tert ‐chloro‐terminated functional PIB chains reaction …”
Section: Introductionmentioning
confidence: 99%